PENATAAN MANAJEMEN SUPLAI BAHAN BAKU KOPI UNTUK KELANGSUNGAN USAHA KOPI BUBUK DI KECAMATAN MUARA SAHUNG - M Mustopa Romdhon; Bandi Hermawan; Alnopri . (DHARMA RAFLESIA, 2017)
Production of coffee beans in the weekly market reaches 95 tons per week. The main problem faced by the business group is the limited availability of raw materials ofselectively red coffee beans. This is because the coffee harvest only occurs in April toAugust, so that outside these months the raw materials are not available. Therefore, thestudy of the raw material supply management and ground coffee marketing managementarrangement that continuous ground coffee business needs to be done. Descriptiveresearch is conducted in this study, in order to describe in detail the actual situation. Datawas obtained from the results of in-depth interviews (depth interviews), observation, anddocumentation of the farmer and member of the group management. The study revealedthat the availability of raw materials of selectively red coffee beans quotation results isvery limited. Raw material needs can be supplied by local purchases of villages in MuaraSahung or from other coffee production center in the District of Kaur. This effort can beachieved through compliance management raw material supply and marketingmanagement arrangement.Keywords: management, raw materials, coffee powder